İmam Muhammed'in El-Asl isimli eserinin Mütûn-i Erbaa'ya tesiri (Kitâbü'l Beyʻ örneği) - Demir, Oğuzkağan (My University, 2014)
İmam Muhammed’in el-Asl İsimli Eserinin Mütûn-i Erbaa’ya Tesiri ismini taşıyan bu tezde, el-Asl'ın mütûn-i erbaa'ya hangi yönlerden tesir ettiği incelenmiştir. Tez giriş, iki bölüm ve sonuçtan oluşmaktadır. Giriş bölümünde tezin konusu, tezin sınırlandırılması, tezin önemi ve amacı, tezin yöntemi ve kaynakları hakkında bilgi verilmiştir. Birinci bölümde el-Asl, Vikâyetü’r-rivâye, el-Muhtâr, Mecmau’l-bahreyn ve Kenzü’d-dekâik’in tanıtımı yapılıp müellifler hakkında kısa bilgiler verilmiştir. İkinci bölüm iki kısma ayrılmıştır. Birinci kısımda el-Asl’ın mütûn-i erbaa’ya şekil açısından tesiri ele alınıp eserlerin sistematiğini oluşturan kitâb, bâb, fasıl ile dil ve üslupları hakkında genel bilgi verilip aralarında mukayese yapılmıştır. İkinci kısımda mütûn-i erbaa’nın kitâbü’l-beyʽ bölümünde yer alan konular tercüme edilerek bu konuların el-Asl’da var olup-olmadığı tespit edilmeye çalışılmış, el-Asl'da olan kısımların el-Asl'da ne şekilde zikredildiği mütûn-i erbaa’ya kıyas edilerek değerlendirmeye tabi tutulmuştur. Sonuç olarak el-Asl ile mütûn-i erbaa'nın farklı dil ve üsluplara sahip olduğu, mütûn-i erbaa'da kullanılan kitâb ve bâb başlıklarının biri hariç tamamının el-Asl'da kullanıldığı, mütûn-i erbaa'da geçen meselelerin yüzde yetmişinin el-Asl'da bulanabileceği tespit edilmiştir.

In this thesis being called as The İnfluence of Imam Muhammad's al-Asl on Mutun-i Arbaa, was examined in which aspects al-Asl impressed on mütûn-i erbaa (four fundamental Hanafi books). The thesis is consisted of an introduction, two chapters and a conclusion. In the introduction, some information was given about the topic of the thesis, its limitation, importance and aim and, the method of the study and the resources. At the first chapter, al-Asl, Vikâye er-Rivâye, al-Muhtâr, Mecmau al-Bahreyn and Kenz ed-Dekâik were promoted Then a helpful brief information was given about the authors.The second chapter was divided into two sections. At the first section, the impression of al-Asl on mütûn-i erbaa with regards to form was dealed. After that, a guideline was given about kitab, bab, fasl (different section of fıqh books) which constitutes the systematic of these books and language and expression. Then these books were compared in terms of all these aspects to the another. At the second section, the subjects that are existed in the kitab al-bay‘ in the mütûn-i erbaa were translated to Turkish and it was tried to be determined whether these subjects existed in the el-Asl as well or not? and How are these subjects mentioned in the al-Asl by the. Comparison with mütûn-i erbaa. In conclusion, it was determined that al-Asl and mütûn-i erbaa have different languages and expressions, all titles of kitab and bab sections in mütûn-i erbaa are used in al-Asl but one, and also that %70 of matters in mütûn-i erbaa maye be found in al-Asl too. ANAHTAR SÖZCÜLER: Nonalkolik yağlı karaciğer hastalığı, nonalkolik steatohepatit, inflamasyon, miyeloperoksidaz, kalprotektin ABSTRACT Serum Levels and Liver Distribution of Myeloperoxidase and Calprotectin in NASH Patients Background: Non-Alcoholic Fatty Liver Disease (NAFLD) includes a broad spectrum of abnormalities ranging from accumulation of fat (also known as simple steatosis) towards non-alcoholic steatohepatitis (NASH) with inflammation. Inflammation and oxidative stress play crucial role in the pathogenesis of NAFLD.Hepatic neuthrophyl infiltration increases in NASH. Myeloperoxidase (MPO) and calprotectin are two of major neuthrophyl activation markers. MPO is also important enzyme which produces free oxigenic radicals. Aim: The study was designed to compare the serum level of MPO and calprotectin in NASH patients and healthy control. Furthermore,we also aimed to investigate if there is any correlation between the MPO and calprotectin staining cell distribution in the liver immunohistochemically and the histological activity. Methods: Fourty eight biopsy-proven NASH patients and twenty five healthy controls were included in the study. The histological disease severity was classified according to NAFLD activity scoring system. Serum MPO and calprotectin levels measured by ELISA. MPO and calprotectin specific immunohistochemical staining was performed to the liver biopsies and those cells staining positive were counted. Results: There was not significant difference between serum levels of MPO of NASH patients and healthy control (14,5 ± 7,5 and 16,2 ± 7,1 ng/ ml, respectively, p=0,259). The serum Calprotectin level of NASH patients was significantly lower than that of the control group ( 1044 ± 847 and 1626 ± 964 ng/ ml respectively, p=0,005). There was not significant difference between MPO and calprotectin staining positive cells distrubition in NASH patients having definitive (NASH score ≥5) or borderline NASH (NASH score 3 or 4) groups (p=0,910 and p=0,642, respectively). Conclusion: Our findings showed that MPO and caprotectin which are the markers of neutrophil activation have not increased in the serum of NASH patients compared to healthy controls despite the ongoing neutrophilic inflammation in liver. Furthermore, the histological severity of NASH has not correlated with the hepatic immunohistochemical staining of those markers in liver biopsies. Thus, the hepatic vii inflammation accompanied by underexpression of peripheral neutrophilic activity markers suggests immune dysfunction as reflected by neutrophil malfunctioning in NASH. Our findings warrant further evaluation with other immunological markers
Keywords: İslam Dini; İslam Hukuku; Tarih